Hydrogen production with grid-connected electrolysis: scenario-based analysis of the EU criteria for renewable fuels - Bernhard Thaler; Gerhard Pirker; Nicole Wermuth (Environmental Research Letters)
Renewable hydrogen (H _2 ) will play a pivotal role in the decarbonization of the energy and industrial sectors. However, during the transition to a clean energy system, the production of H _2 with electrolysis runs the risk of increasing carbon dioxide (CO _2 ) emissions if the electricity system is still partly based on fossil fuels. The European Union has set ambitious targets for the production of H _2 and defined strict rules in delegated acts to the renewable energy directive, when H _2 produced with public grid electricity can be counted as renewable. This paper analyzes two grid criteria central to these rules, renewable energy share and CO _2 emission intensity, in several future scenarios of the European energy system. By uniquely focusing on the impact of H _2 production from the perspective of EU grid criteria, this study offers a novel assessment of how these regulations interact with the evolving energy landscape. Fulfillment of the renewable H _2 grid criteria strongly depends on the future build-out of renewable energy resources, electricity demand, and amount of domestically produced H _2 . In a scenario with ambitious renewable build-out until 2030, represented by current drafts of national energy and climate plans, many countries will meet the stated criteria. However, adding a high amount of domestically produced H _2 partly cancels out this effect. In a scenario with reduced renewable build-outs, comparable to historically achieved renewable resource additions, many fewer countries achieve the grid criteria. Finally, net CO _2 emission reductions are analyzed by comparing power sector emission changes with the opportunity emissions that result from fossil fuels replacements with H _2 . The results indicate that using H _2 in CO _2 intensive use cases can lead to emission reductions, even if grid criteria are below the thresholds defined in the delegated acts. However, reduced renewable energy expansion poses the risk of not achieving any emission reductions at all with the produced H _2 .